High sensitivity rotating alternating current field measurement for arbitrary-angle underwater cracks. (April 2016) - Li, Wei; Yuan, Xin'an; Chen, Guoming; Ge, Jiuhao; Yin, Xiaokang; Li, Kongjing
Abstract: Alternating current field measurement (ACFM) technology has been used for sizing underwater structure cracks. However, conventional ACFM is more sensitive to cracks perpendicular to the induced current than cracks with other angles. In this paper, a rotating alternating current field measurement (RACFM) method and underwater test system are present for the detection of arbitrary-angle cracks with high sensitivity. The RACFM is proved by simulations and experiments. Arbitrary-angle cracks detection results obtained from ACFM and RACFM have shown that the RACFM method overcomes the limitation of directional detection of ACFM and effectively achieves high detection sensitivity for arbitrary-angle cracks on underwater structures. Highlights: The RACFM is proved through simulations and experiments. RACFM can break the limitation of directional detection of ACFM. RACFM can detect arbitrary-angle underwater cracks effectively and sensitively.